2007
DOI: 10.2105/ajph.2006.087197
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Past-Year Mental Health Service Use Among Latinos: Results From the National Latino and Asian American Study

Abstract: Rates of mental health service use among Latinos appear to have increased substantially over the past decade relative to rates reported in the 1990s. Cultural and immigration characteristics should be considered in matching mental health services to Latinos who need preventive services or who are symptomatic but do not fulfill psychiatric disorder criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
270
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 342 publications
(284 citation statements)
references
References 40 publications
10
270
2
2
Order By: Relevance
“…Findings suggest that patterns of longitudinal association between CMCs and depressive symptoms may depend on race in the USA. Our study provides longitudinal evidence supporting the Black-White health paradox [8,9], defined as a higher rate of CMCs [1,2] but lower prevalence of depression or depressive symptoms [1][2][3][4][5][6][7][8][9][10] among Blacks compared to Whites. Our findings are supported by the results reported by Capistrant and colleagues who showed that although among Whites and Blacks depressive symptoms are associated with cardiovascular mortality, the association between baseline depressive symptoms and subsequent cardiovascular mortality was only significant for Whites, but not Blacks, after adjusting for covariates [37].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Findings suggest that patterns of longitudinal association between CMCs and depressive symptoms may depend on race in the USA. Our study provides longitudinal evidence supporting the Black-White health paradox [8,9], defined as a higher rate of CMCs [1,2] but lower prevalence of depression or depressive symptoms [1][2][3][4][5][6][7][8][9][10] among Blacks compared to Whites. Our findings are supported by the results reported by Capistrant and colleagues who showed that although among Whites and Blacks depressive symptoms are associated with cardiovascular mortality, the association between baseline depressive symptoms and subsequent cardiovascular mortality was only significant for Whites, but not Blacks, after adjusting for covariates [37].…”
Section: Discussionmentioning
confidence: 69%
“…Compared to Whites, Blacks have a higher prevalence of chronic medical conditions (CMCs) [1,2] but lower levels of clinical and subclinical depression [1][2][3][4][5][6][7][8], a phenomenon which has been labeled the Black-White health paradox [9,10]. In line with this phenomenon, a number of studies have shown that Blacks and Whites differ in the magnitude of the association between various CMCs and depression or depressive symptoms [11][12][13][14] suggesting that race may moderate the reciprocal associations between CMCs and depression.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previous research indicating that Latinos underutilize mental health services, 31 particularly those who have resided in the US for a short period of time. 31,32 Several limitations are evident, including the unstable prevalence estimates and the small sample sizes, which raise concern about adequate power to detect meaningful differences in this sample. Diagnoses were also based on unvalidated, fully structured lay interviews where lifetime prevalence was assessed retrospectively.…”
Section: Resultsmentioning
confidence: 99%
“…Language preference may influence MH care use. 34 VA now collects data on preferred language; however, that was not available at the time of this study, and this study was not powered to examine the influence of language preference. Despite these limitations, the relative relationship between PTSDpositive status and MH services use that we detected is likely to reflect true associations in the U.S. women veteran population.…”
Section: Discussionmentioning
confidence: 99%